Post-earthquake fire behavior and performance-based fire design of steel moment frame buildings. (February 2021) - Alasiri, Muhannad R.; Chicchi, Rachel; Varma, Amit H.
Abstract: This paper presents an assessment of steel buildings subjected to post-earthquake fire, illustrated through the implementation of a ten-story case study building, which was designed in accordance with U.S. design codes. The building is located in a high seismic region (Los Angeles, CA), and designed for the associated seismic hazard levels using perimeter special moment frames (SMFs) to resist lateral (wind and seismic) loading and gravity interior frames with composite floor systems to resist gravity (dead and live) loading. The entire 3D building structure was idealized and analyzed using finite element models capable of modeling inelastic deformations, instability failures, and connection damage due to earthquakes and fire. The building models were subjected to eleven earthquakes followed by three different fire scenarios to simulate the effects of post-earthquake fires. The results from post-earthquake fire analyses were used to assess the impact of earthquake-induced damage on structural behavior and stability during fire. Assessments indicate that, for the type and design of structure considered in this research, earthquake-induced damage is generally limited to the perimeter moment frames and has limited influence on post-earthquake fire performance, which is governed by the strength and stability of gravity columns and floor systems. Analytical parametric studies were conducted to further assess and develop performance-based design guidelines for improving structural behavior and stability during post-earthquake fires. These studies indicate that partial or full collapse of the building structure can be prevented by sufficiently increasing the structural design (size) or fire protection (fireproofing thickness) of the critical gravity columns. Graphical abstract: Unlabelled Image Highlights: Presents a numerical methodology for assessing effects of cascading hazards, namely post-earthquake fire, on the performance of steel moment frame buildings. When exposed to post-earthquake fires, gravity columns remain the most critical components in steel moment frame buildings. Uniform heating of gravity columns is more detrimental to performance than thermal gradients through the cross-section. Increasing fire protection thickness on gravity columns, or increasing the structural design (size) of gravity columns can prevent collapse initiation.